Flipped Classroom: un modelo pedagógico para el aprendizaje de la física en el bloque curricular movimiento y fuerza - Agila Malla, Jimmy Stalin (2023)
With the implementation of virtual classes due to the COVID-19 pandemic, education has undergone several changes, including the application of new methodologies, the continuous use of TICS with technological advances, which has led to adjustments or modifications in the development of classes. For this reason, the present research allows determining the influence of the Flipped Classroom pedagogical model in the teaching-learning process of the curricular block movement and strength, it is developed with a quantitative research approach of explanatory type and a quasi-experimental design, The population represents the first year students of General Unified High School of the Educational Unit "Vicente Anda Aguirre" period 2021-2022, a non-probabilistic sampling of intentional type is considered and the first year students of high school parallel A are selected, the objective test was used as an instrument for data collection presented in two tests: pre-test and post-test, applied to the control and quasi-experimental groups, data collection was done through the Google Forms platform and processed through the statistical software SPSS and R studio. Based on the significance effect size obtained from the data, it is proven that there is a difference in means between the control and experimental groups, i.e. the academic performance of the experimental group was statistically significant and positively superior to that of the control group, which means that the Flipped Classroom pedagogical model significantly influences the teaching and learning development process of the movement and strength curricular block, which leads to determine significant and lasting learning.